Analysis of the Playing Technique Skills of the English Manchester City Football Club in Winning the UEFA Champions League Title For the 2022-2023 Season - Joe Pratama Saragih; Achmad Widodo; Mokhamad Nur Bawono; Awang Firmansyah (Populer: Jurnal Penelitian Mahasiswa, 2024)
Football is a popular sport that appeals to the public. The purpose of the study was to determine the most dominant playing technique skills and quality of playing techniques from the Manchester City Team. The type of research used is quantitative descriptive research with a descriptive method approach. The subjects used in the study were all players who played in the match between Manchester City against Sevilla in the group, RB Leipzig in the last 16, Bayern München in the last 8, Real Madrid in the last 4, and Inter Milan in the final. While the object of this research concerns playing technique skills such as: passing, shooting, dribbling, ball control, and heading.It can be concluded from the results of the analysis of the Manchester City team in five matches in the UEFA Champions League season 2022-2023, namely: The average percentage of the most dominant and best techniques used by the Manchester City team is passing 564 times (88%%), shooting 17 times (54%), dribbling 26 times (62%), ball control 427 times (96%) and heading 21 times (53%), The most dominant technique used by the Manchester City team in the five matches was the passing technique 2,818 times and the ball control technique was the technique that had the highest quality (96%) compared to other techniques, The average percentage of Manchester City team techniques against all opponents, seen from the percentage of playing technique skills, the Manchester City Team excels in all playing techniques such as passing (by 6%), shooting (by 20%), dribbling (by 16%), ball control (by 2%) and heading (by 6%). Based on statistical data on all playing technique skills of the Manchester City team and their opponents, overall (first half, second half and full time) the percentage of Manchester City team playing techniques only lost in one aspect of the technique, namely heading techniques (by 1% in the second half) the rest were able to excel, both in the first half, second half, and in full time, this proves that the percentage of successful passing, shooting, dribbling, ball possession and heading techniques can have an influence on the final result of the match. But in addition to the techniques possessed by players, there are other factors that affect the outcome of the match, such as: game tactics, understanding of game strategy, formation and mental factors.